2011
DOI: 10.1016/j.ajodo.2010.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Stability of rapid maxillary expansion and facemask therapy: A long-term controlled study

Abstract: Introduction: The aim of this prospective controlled study was to evaluate the long-term effects of rapid maxillary expansion and facemask therapy in Class III subjects. Methods: Twenty-two subjects (9 boys, 13 girls; mean age, 9.2 years 6 1.6) with Class III disharmony were treated consecutively with rapid maxillary expansion and facemask therapy followed by fixed appliances. The patients were reevaluated at the end of the 2-phase treatment (mean age, 14.5 years 6 1.9) and then recalled about 8.5 years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
88
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 25 publications
22
88
1
7
Order By: Relevance
“…In the maxilla, Co-point A increased similarly in both groups, although the control group also showed a significant increase in the Point A to Nasion perpendicular distance. Therefore, there was no apparent tendency to relapse in the sagittal position of the maxilla, as was described in Masucci et al 8 In the study by Pangrazio-Kulbersh et al, 26 the positive changes found in the anteroposterior position of the maxilla remained stable over time.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the maxilla, Co-point A increased similarly in both groups, although the control group also showed a significant increase in the Point A to Nasion perpendicular distance. Therefore, there was no apparent tendency to relapse in the sagittal position of the maxilla, as was described in Masucci et al 8 In the study by Pangrazio-Kulbersh et al, 26 the positive changes found in the anteroposterior position of the maxilla remained stable over time.…”
Section: Discussionmentioning
confidence: 55%
“…[5][6][7] Yoshida et al 7 found that the combined use of a maxillary protraction appliance and a chincup was effective in correcting intermaxillary and interarch discrepancies, although moderate rebound-like changes occurred in mandibular size and position at the end of pubertal growth. Masucci et al 8 evaluated the longterm stability of RME and face mask therapy after active circumpubertal growth; in the long term, approximately 73% of the Class III patients achieved successful outcomes. Skeletal changes were mainly due to improvements in the sagittal position of the mandible, and initial maxillary changes reverted in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with other orthodontic studies reporting long-term maxillary stability of traditional FM cases. [22][23][24][25]32 Williams et al 33 concluded that the relapse to a Class III pattern was primarily a result of mandibular growth rather than a relapse of treatment in the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 On the other hand, no data are available with regard to the outcomes of surgical assistance during maxillary protraction with FM therapy when active craniofacial growth is complete. This information is very important for patients being treated with these protocols, because a significant tendency toward reestablishment of the Class III growth pattern has been widely demonstrated after active protraction therapy, 24,25 and pubertal growth tends to last longer in Class III subjects compared to Class I subjects.…”
Section: Introductionmentioning
confidence: 99%
“…13 Traditional orthopedic treatments include palatal expansion devices and extraoral appliances, such as headgears and face masks. 14,15 Recently, mini-implants have been applied with palatal expanders to achieve greater sutural expansion. 8,16 With the broadened application of the mini-implants used in orthodontics, there is a need to examine the stability of these implants under various clinical conditions.…”
Section: Introductionmentioning
confidence: 99%